57 The Use of the Physiological Profile Assessment to Improve Prediction of Fragility Fractures in Community-Dwelling Older People. (20th December 2019) - Harvey, Lara; Taylor, Morag; Delbaere, Kim; Lord, Stephen; Brodaty, Henry; Kochan, Nicole; Sachdev, Perminder; Mitchell, Rebecca; Close, Jacqueline
Abstract: Introduction: The Physiological Profile Assessment (PPA) is a validated composite measure of sensorimotor function, known to predict falls with 75% accuracy. This work aimed to investigate whether PPA is also associated with fragility fractures. Method: Participants were 489 community-dwelling older people (age=70-90) enrolled in the longitudinal population-based Sydney Memory and Ageing Study. Participants underwent comprehensive assessments at enrolment, including the 5-item PPA (visual contrast sensitivity, lower limb proprioception, knee extension strength, simple reaction time and postural sway). Participant records were linked to emergency department, hospital and death records (2005-2014) to identify fragility fractures following baseline assessment, with median follow-up duration of 7.5 years. Negative binomial regression, with observation time as the offset, was used to assess factors associated with fractures. Results: At baseline assessment, 281 (57.5%) participants were assessed as having low/mild fall risk [PPA<1] and 208 (42.5%) as moderate/marked/very marked fall risk [PPA score > 1]. Over the study period, 72 (14.7%) individuals sustained 1 fracture, and a further 39 (8.0%) sustained 2 or more fractures. Univariate analysis showed that increasing age (Incidence Rate Ratio (IRR) 1.1, 95%CI 1.0-1.1, p=0.0026), being female (IRR 1.8, 95%CI 1.3-2.8, p=0.0033), having osteoporosis (IRR 1.7, 95%CI 1.1-2.6, p=0.0340) and moderate/marked/very marked PPA (IRR 1.8, 95%CI 1.2-2.7, p=0.0025) were associated with fractures. In the multivariate analysis, only moderate/marked/very marked PPA (IRR 1.6, 95%CI 1.1-2.5, p=0.0159) and being female (IRR 1.8, 95%CI 1.1-2.8, p=0.0121) remained independently associated with fractures. Conclusion: These findings show that people at increased risk of falls based on the Physiological Profile Assessment are also at increased risk of future fragility fractures regardless of the presence of osteoporosis. Early identification of this high risk population provides the opportunity to intervene with evidence based strategies to minimize falls risk as well as considering pharmacological management of bone health.